Neuro-Ophthalmology – An Approach to Common Cases in the Outpatient Department - Shalin Shah; Paromita Dutta (Delhi Journal of Ophthalmology)
Neuro-ophthalmology patients present with nonspecific complaints and are often missed in the outpatient department (OPD). This review systematically outlines the basics of clinical examination essential for picking up subtle clinical signs and corroborating the findings to arrive at a provisional diagnosis. These patients require a multidisciplinary approach to management. A high degree of clinical suspicion, appropriate clinical history, and examination, imaging, or systemic workup if needed, can aid in early diagnosis of neuro-ophthalmology cases. We also add a note about commonly seen neuro-ophthalmology cases in the OPD.